2023
DOI: 10.1017/s1743923x22000502
|View full text |Cite
|
Sign up to set email alerts
|

All Politics Is Local: Studying Women’s Representation in Local Politics in Authoritarian Regimes

Abstract: The past decade has witnessed a significant increase in women’s presence in local politics. According to the newly published United Nations (UN) Women in Local Government data set, women constitute 36% of local deliberative bodies worldwide compared to merely 25% in national parliaments.1 Much of this increase is the result of gender quotas: the Gender Quotas Database (International IDEA 2022) shows that as of 2021, 75 countries had some form of gender quota on the local level, 24 of which were authoritarian r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…According to Homsy and Lambright [13], there is a growing body of research examining factors associated with gender in local government practices [14,15], but little is known about the influence of characteristics of the leaders of these bodies. Further, research has shown that factors such as the use of networking and affinity bias (the tendency for individuals to favour people who share similar characteristics or interests) contribute to the dominance of men in leading positions [16], and also at the local level of politics [17].…”
Section: Introductionmentioning
confidence: 99%
“…According to Homsy and Lambright [13], there is a growing body of research examining factors associated with gender in local government practices [14,15], but little is known about the influence of characteristics of the leaders of these bodies. Further, research has shown that factors such as the use of networking and affinity bias (the tendency for individuals to favour people who share similar characteristics or interests) contribute to the dominance of men in leading positions [16], and also at the local level of politics [17].…”
Section: Introductionmentioning
confidence: 99%